WATERING OF PASTURE TERRITORIES OF KAZAKHSTAN FOR SUSTAINABLE DEVELOPMENT OF - Jarassova Jamal; Zhakupova Zhanar (Research Retrieval and Academic Letters, 2024)
The forecast parameters of agricultural production show that by 2050 the republic will have the economic potential to develop the industry to fully meet the needs of the population of the country and regions in all basic food products. The regions of the Republic of Kazakhstan located in semi-desert and desert zones will specialize in meat production. Therefore, it is necessary to create a geoinformation database and a geoinformation and analytical system aimed at solving the problems of sustainable development of animal husbandry in conditions of climatic and anthropogenic changes. In order to ensure the country’s food security in low-water years, with a decrease in surface water resources, practical recommendations will be developed to ensure the watering of pastures at the expense of fresh and low-mineralized groundwater. This will allow improving the conditions for watering pastures with a shortage of surface water sources for the development of domestic livestock. The proposed technical solutions for the water supply of pasture areas from underground water sources will have a number of advantages compared to surface waters: groundwater has better quality, is more reliably protected from pollution and contamination, is less susceptible to seasonal and long-term fluctuations, practically does not affect the environment during operation.